A Fuzzy Approach on Earned Value Method to Evaluate Project Performance in Solojebres Commuter Depot - Ahmad Kahfi Firdausi; M. Ruslin Anwar; Arief Rachmansyah (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2024)
The high level of public interest in using the Solo-Jogja commuter needs to be accompanied by an effort to improve the services and reliability of facilities, one of which is the establishment of a Commuter Depot located at Solojebres Station. In the 18th month of work, the construction of the Commuter Depot experienced delays in work performance with a deviation between plan progress and actual progress of -3.5415%. This research aims to evaluate project performance, including the project's cost and schedule performances, and estimate the cost and schedule of the project at completion due to delays that occur using the Earned Value Method with a fuzzy approach. The required data are the Budget Plan, Weekly Project Report, S-curve, and Actual Cost data. Based on the analysis result, until the 18th month of work, obtained the total Planned Value of IDR 64,581,925,585 (simplified to IDR 6,458.2), the total Actual Cost of IDR 63,954,955,399 (simplified to IDR 6,395.5), the total Fuzzy Earned Value of IDR 62,740,381,379.42 (simplified to IDR 6,274.0), the Cost Performance Index indicates that the project is ahead of budget condition, the Schedule Performance Index indicates that the project is behind schedule condition, the Cost Estimate at Completion of IDR 96,048,508,686 with the cost needed to complete the rest of work of IDR 32,093,553,287 and the Schedule Estimate at Completion of 27.03 months with the time required to complete the rest of work of 9.03 months.